Robust Estimation of beta and the hedging ratio in Stock Index Futures In the Integrated Latin American Market (2017)
This paper examines the effect exerted by outliers in the equity betas in the Integrated Latin American Market (MILA), estimated by two different methods: ordinary least squares (OLS) and robust estimation (RMM). To illustrate the empirical relevance of the estimated betas, we evaluate the hedging ratio using stock index futures. The results indicate that the estimates made by the RMM method provide a better fit and increase the efficiency of a hedging strategy when there are outliers in the estimation window of beta.